2011
DOI: 10.3354/ab00357
|View full text |Cite
|
Sign up to set email alerts
|

Invading the Adriatic: spatial patterns of marine alien species across the Ionian–Adriatic boundary

Abstract: An important pathway of introduction of alien marine species in the Adriatic seems to be the northward expansion of species already established in the Ionian Sea, aided by the East Adriatic Current. We modelled the occupancy of alien marine species in the upper infralittoral zone of rocky bottoms across the Ionian-Adriatic border (Albanian and Montenegrin coastlines), based on underwater visual survey data. A method that took into account imperfect detection of the target species was applied to make unbiased o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…cylindracea was firstly registered in the central Adriatic in 2000 (Žuljević et al, 2003), while in the southern Adriatic (Montenegro) in 2004 (Mačić, 2005). In addition, for several alien species Katsanevakis et al (2011b) found a general pattern of declining occupancy from the northern Ionian Albanian coast towards the SE Adriatic. Affinity and chances of alien establishment in the Southern Adriatic will increase if sea temperature continues to increase and already established species in the central Mediterranean are in expansion.…”
Section: The Alien Sea Harementioning
confidence: 92%
See 1 more Smart Citation
“…cylindracea was firstly registered in the central Adriatic in 2000 (Žuljević et al, 2003), while in the southern Adriatic (Montenegro) in 2004 (Mačić, 2005). In addition, for several alien species Katsanevakis et al (2011b) found a general pattern of declining occupancy from the northern Ionian Albanian coast towards the SE Adriatic. Affinity and chances of alien establishment in the Southern Adriatic will increase if sea temperature continues to increase and already established species in the central Mediterranean are in expansion.…”
Section: The Alien Sea Harementioning
confidence: 92%
“…Considering the long duration of the species' veliger stage (Emore, 2002), as well as the occurrence of northward currents along the SE Adriatic coast (Marini et al, 2010), the spread of A. dactylomela in the Adriatic Sea appears to be inevitable, as is true for many other alien species (Katsanevakis et al, 2011b). Nevertheless, A. dactylomela has already been recorded (2006) from Croatia, further north in the Adriatic Sea than the present record (Turk, 2006;Despalatović et al, 2008).…”
Section: The Alien Sea Harementioning
confidence: 99%
“…In the general formulation by MacKenzie et al (2002), the presence/ absence of a species at a given number of s sites is recorded K times by the same or independent observers. In the approach proposed by Katsanevakis et al (2011), and more recently applied by Issaris et al (2012) and Salomidi et al (2013), the replication of sampling through time is replaced by repeated independent observations by different observers. Detections by each single observers are considered as surveys sensu MacKenzie et al (2006), generating, for each study site, a detection history consisting of a string of 1 (detection) and 0 (nondetection).…”
Section: Modelling Species Occupancy and Detection Probability From Smentioning
confidence: 99%
“…The wrasse, Symphodus rostratus, was used as a model species, since, in contrast to most of the other species, it was not detected at all sampling sites. The occupancy of S. rostratus was modelled by following the approach proposed by Katsanevakis et al (2011), which expands the single-season procedures developed by MacKenzie et al (2002MacKenzie et al ( , 2006. In the general formulation by MacKenzie et al (2002), the presence/ absence of a species at a given number of s sites is recorded K times by the same or independent observers.…”
Section: Modelling Species Occupancy and Detection Probability From Smentioning
confidence: 99%
See 1 more Smart Citation